Incidencia del proyecto educativo institucional en el proceso de enseñanza- aprendizaje del colegio nacional técnico Ingeniero José Corsino Cárdenas del cantón Pasaje, periodo lectivo 2012- 2013, y la propuesta alternativa de capacitación a directivos y docentes para la elaboración del PEI. - Jaramillo Moreno, Guillermo Humberto (2015)
The problem you have in educational institutions today is that education authorities on whether school management have the institutional educational project (PEI) being a management tool focused on the student, the same one that has a high incidence in the processes teaching and learning that demonstrate pedagogical and didactic skills used by teachers for become a counselor and dynamic resource that should help the educational community to integrate all actions of the educational institution towards improving the learning of students, but this instrument has a low level of development, worse in some educational institutions do not even have the same preventing have their own identity, others have but outdated, subutilizad, copied with other contextual and community reality, this is due to carelessness by education authorities to apply a methodology of participatory construction of PEI.